Floristic composition, biological spectrum, and phytogeographic distribution of the Bin Dara Dir, in the western boundary of Pakistan - Manan, Fazal; Khan, Shujaul Mulk; Muhammad, Zahir; Ahmad, Zeeshan; Abdullah, Abdullah; Rahman, Amjad ur; Han, Heesup; Ariza-Montes, Antonio; Contreras-Barraza, Nicolás; Raposo, António (Frontiers in Forests and Global Change, 2022)
This study assesses the floristic composition, biological spectrum and phytogeographical elements of the Bin Dara western boundary of Pakistan. The flora consists of 140 plant species belong to 47 families. The most dominant family was Poaceae (with 14 species), followed by Asteraceae (11 species). The biological spectrum showed the therophytes (71 species with 50.71%) as dominant life form class, followed by mega-phanerophytes (27 species, 19.28%), nano-phanerophytes (15 species, 10.71%), geophytes (10 species, 7.14%), chamaephytes (9 species, 6.42%) and hemi-cryptophytes (8 species, 5.71%). Leaf size classes comprised of nanophylls (48 species with 34.28%), microphylls (32 species, 22.85%), mesophylls (22 species, 15.71%), macrophylls (17 species, 12.14%), leptophylls (12 species, 8.57), megaphylls (8 species, 5.75%) and aphyllous (1 species, 0.71%). Cosmopolitan was most prominent form of phytogeographic elements (with 17 species, 12.14%), followed by pantropical and euro sibirian-mediterranean-irano turanian (14 species, 10%) each. The pluriregional represent (13 species, 9.28%), holarctic and mediterranean- irano turanian (10 species, 7.14%), irano turanian and western himalayan (9 species, 6.42%) each. It is recommended that further study is needed to map the vegetation, its indicator and rare species that face a huge threat of endangerment.